Annexin A7 Regulates Endometrial Receptivity - Alauddin, Md; Salker, Madhuri S.; Umbach, Anja T.; Rajaxavier, Janet; Okumura, Toshiyuki; Singh, Yogesh; Wagner, Anna; Brucker, Sara Y.; Wallwiener, Diethelm; Brosens, Jan J.; Lang, Florian (Frontiers in Cell and Developmental Biology, 2020)
A limited window of receptivity is a prerequisite of reproductive success. Indispensable receptivity genes include cyclooxygenase 2 (COX2), an enzyme accomplishing formation of prostaglandin E2 (PGE2). A powerful regulator of PGE2 formation is Annexin A7 (ANXA7). The present study thus explored whether ANXA7 impacts on implantation and fertility. Here we show that ANXA7 is expressed in endometrial tissue and increases upon decidual transformation of human endometrial stromal cells (HESCs) in a time-dependent manner. Silencing ANXA7 significantly decreased the expression of PRL and IGFBP1, canonical decidual marker genes, but enhances COX2 and PGE2 levels. Genetic knockout of AnxA7 in mice significantly increases the number of implantation sites and litter sizes. Further, analysis of human endometrial biopsies showed that ANXA7 transcript and protein levels are decreased during the midluteal window of implantation in women suffering from recurrent pregnancy loss when compared to subfertile patients. Taken together, the data indicate that ANXA7 has a conserved role in regulating endometrial receptivity and implantation.